Recent Development and Directions in Printed Perovskite Solar Cells. Issue 6 (30th January 2022) - Samantaray, Nita; Parida, Bhaskar; Soga, Tetsuo; Sharma, Ambika; Kapoor, Avinashi; Najar, Adel; Singh, Arjun
Abstract : Just over a decade ago, perovskite solar cells (PSCs) established themselves as the next generation of photovoltaic technology due to their comparably higher power conversion efficiency (PCE) (25.6%), cheaper and simpler manufacturing processes to that of Silicon solar cells. Based on the potential, several methods and processes have been developed to produce high‐quality perovskite films for commercialization of PSCs. It has recently been found that printing technology is very effective in controlling film formation, resulting in a high PCE of over 21%. This review summarizes the intense research that has been done on newer printing techniques to enlarge perovskite films and other layers such as the hole transport layer (HTL), the electron transport layer (ETL), and electrodes for PSCs. At the end, the review article describes the future scope of research to address the challenges of commercializing PSCs. Abstract : The current increasing demand of renewable energy attracts the scientific community toward solar energy as one of the alternative sources of energy. This review summarizes the current status of large area printable perovskite solar cells (PSCs) and outlines possible strategies for moving towards commercialization of low‐cost PSCs.